2007
DOI: 10.1002/nur.20232
|View full text |Cite
|
Sign up to set email alerts
|

Health outcomes associated with potentially inappropriate medication use in older adults

Abstract: The purpose of this study was to examine the prevalence of potentially inappropriate medication use (PIMs) among community-dwelling older adults and the association between PIMs and health care outcomes. Participants were 17,971 individuals age 65 years and older. PIM use was defined by the Beers criteria. Drug-related problems (DRPs) were defined using ICD-9 codes. Forty percent of the 17,971 individuals filled at least 1 PIM prescription, and 13% filled 2 or more PIM prescriptions. Overall DRP prevalence amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
208
4
25

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 257 publications
(247 citation statements)
references
References 42 publications
10
208
4
25
Order By: Relevance
“…53 Among the positive aspects of using the Beers list are the facts that it can be adapted to computer systems, it enables pharmacoepidemiological studies on large populations, it incorporates information from the specialized literature and from specialists' consensuses, and it can easily be used for educational purposes. 2,49 To obtain the results from this study, a spreadsheet generated through a database was used. The advantages of using a computerized database for investigating prescribed medications include the accuracy of registering what was prescribed and the fact that it does not depend on information supplied by patients.…”
Section: 51mentioning
confidence: 99%
See 2 more Smart Citations
“…53 Among the positive aspects of using the Beers list are the facts that it can be adapted to computer systems, it enables pharmacoepidemiological studies on large populations, it incorporates information from the specialized literature and from specialists' consensuses, and it can easily be used for educational purposes. 2,49 To obtain the results from this study, a spreadsheet generated through a database was used. The advantages of using a computerized database for investigating prescribed medications include the accuracy of registering what was prescribed and the fact that it does not depend on information supplied by patients.…”
Section: 51mentioning
confidence: 99%
“…1 The presence of many comorbidities, high consumption of medicines, fragmented care, physiological changes and socioeconomic factors, among other factors, make it common for problems relating to medicines to arise among this population. 2 This concern regarding the impact of prescriptions among an aging population has led to the creation of several strategies for dealing with this phenomenon. Among these is the detection of potentially inappropriate medicines (PIMs).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Potentially inappropriate medication (PIM) are those medications or classes of medications that should be avoided in patients aged ≥ 65 years, since they have no clear evidence-based indication, are not cost-effective [5] , pose unnecessarily high risk for older persons [6] , once the risks of using overcome the benefits [7] , and safer alternatives are available [6,8] . The exposure of older people to PIM is associated with the increased use of health care services [9] , ADR [4,10] and higher medical costs [11] . However, PIM prescriptions are common among these patients [12] , since studies have shown that 24.5% to 66.0% [8,[11][12][13][14][15][16] of older people take these drugs.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] At the same time, adverse drug events are common in this population, resulting in functional impairment and increasing morbidity, mortality, and health care costs. [4][5][6][7] Reported rates of adverse drug events in older populations range from 10% to 30% for ambulatory and inpatients alike. [8][9][10][11][12] Inappropriate prescribing, as indicated by explicit criterion-based or implicit judgment-based measures, increases the occurrence of adverse drug events.…”
Section: Introductionmentioning
confidence: 99%